Contracting for the Second Best in Dysfunctional Electricity Markets - Nikandrova, Arina; Steinbuks, Jevgenijs (World Bank, Washington, DC, 2014)
Power pools constitute a set of sometimes complex institutional arrangements for efficiency-enhancing coordination among power systems. Where such institutional arrangements do not exist, there still can be scope for voluntary electricity-sharing agreements among power systems. This paper uses a particular type of efficient risk-sharing model with limited commitment to demonstrate that second-best coordination improvements can be achieved with low to moderate risks of participants leaving the agreement. In the absence of an impartial market operator who can observe fluctuations in connected power systems, establishing quasi-markets for trading excess electricity through the kind of mechanism described here helps achieve sustainable cooperation in mutually beneficial electricity sharing.